Trend dan punca penggunaan dadah di kalangan penagih dadah wanita di negeri Sabah: Implikasi kepada rawatan dan pemulihan dadah - Marican, Sabitha; Mohamed, Mahmood Nazar; Ismail, Rosnah (Agensi Antidadah Kebangsaan, 2007)
The involvement of women with psychoactive drugs is found to be most serious in the state of Sabah as compared to the other states in Malaysia. The National Anti-Drugs Agency (NADA) ranked Sabah 6th on the severity of incidence of drug addiction with 1,229 drug users identified between the months of January to September, 2005, out of which a total of 686 were women ranging from young adolescents to those in their 40s.Sabahan women drug addicts used drugs not only for its euphoric effect but for various other reasons including to escape from their problems, to maintain their ‘slim’ figures and to remain beautiful. Syabu is the drug of choice for most Sabahan women addicted to drugs because it is cheaper and can be easily obtained as compared to heroin or other drugs. The purpose of this study is to identify the profile of Sabahan women addicted to drugs, the etiology of drug use and the effect of drugs especially on their mental state.This study employed a cross-sectional survey design on a sample of 96 respondents, purposely selected from drug users and addicts presently undergoing drug treatment and rehabilitation at Pusat Serenti Bachok Kelantan, and those incarcerated at the Kota Kinabalu Women Prison, Tawau and Sandakan Prisons. Among the reasons for using drugs is because they were curious of its effects. Other reasons pertain to asjustment.